Promoting electrocatalytic CO2 methanation using a molecular modifier on Cu surfaces. Issue 48 (1st December 2022) - Wang, Cheng; Kong, Xiangdong; Huang, Junming; Yang, Yu; Zheng, Han; Wang, Huijuan; Dai, Suiyang; Zhang, Shuzhen; Liang, Yongxiang; Geng, Zhigang; Li, Fengwang; Zeng, Jie
Abstract : A benzenethiol molecule modulates the electronic structure of copper surfaces and thus tunes the coverage of key reaction intermediates, boosting electrochemical CO2 methanation. Abstract : The electroreduction of CO2 to methane using renewable energy is a promising approach to achieving carbon neutrality. At commercially relevant current densities (>200 mA cm −2 ), methane selectivity is however below 50%. Herein, we reported a benzenethiol-modified Cu nanoparticle catalyst that achieved a methane faradaic efficiency of 54.5% at a partial current density of 383 mA cm −2, 1.9-fold higher than that of Cu nanoparticle controls. In situ vibrational spectroscopy and density functional theory calculations showed that the benzenethiol modulated the electronic structure of the Cu surface to enable a lowered coverage of *CO, favouring the formation of *CHO, a key intermediate embarking on the CH4 pathway, over the competing carbon–carbon coupling, the pathway towards multicarbons.